Influenza Virus Down-Modulates G6PD Expression and Activity to Induce Oxidative Stress and Promote Its Replication - De Angelis, Marta; Amatore, Donatella; Checconi, Paola; Zevini, Alessandra; Fraternale, Alessandra; Magnani, Mauro; Hiscott, John; De Chiara, Giovanna; Palamara, Anna Teresa; Nencioni, Lucia (Frontiers in Cellular and Infection Microbiology, 2022)
Influenza virus infection induces oxidative stress in host cells by decreasing the intracellular content of glutathione (GSH) and increasing reactive oxygen species (ROS) level. Glucose-6-phosphate dehydrogenase (G6PD) is responsible for the production of reducing equivalents of nicotinamide adenine dinucleotide phosphate (NADPH) that is used to regenerate the reduced form of GSH, thus restoring redox homeostasis. Cells deficient in G6PD display elevated levels of ROS and an increased susceptibility to viral infection, although the consequences of G6PD modulation during viral infection remain to be elucidated. In this study, we demonstrated that influenza virus infection decreases G6PD expression and activity, resulting in an increase in oxidative stress and virus replication. Moreover, the down regulation of G6PD correlated with a decrease in the expression of nuclear factor erythroid 2-related factor 2 (NRF2), a key transcription factor that regulates the expression of the antioxidant response gene network. Also down-regulated in influenza virus infected cells was sirtuin 2 (SIRT2), a NADPH-dependent deacetylase involved in the regulation of G6PD activity. Acetylation of G6PD increased during influenza virus infection in a manner that was strictly dependent on SIRT2 expression. Furthermore, the use of a pharmacological activator of SIRT2 rescued GSH production and NRF2 expression, leading to decreased influenza virus replication. Overall, these data identify a novel strategy used by influenza virus to induce oxidative stress and to favor its replication in host cells. These observations furthermore suggest that manipulation of metabolic and oxidative stress pathways could define new therapeutic strategies to interfere with influenza virus infection.